New mapping approach based on reputation model under locator/ID separation protocol - WAN Ming; LIU Ying; ZHANG Hong-ke (Tongxin xuebao)
Through analyzing mapping spoofing which may exist or happen in the incoming mapping theory under loca-tor/ID separation protocol,a new mapping approach to relieve the thread of mapping spoofing was proposed.This ap-proach introduced the reputation model based on feedback evaluation into the mapping theory and increased the trust-worthiness of the mapping information by means of the dynamic trust evaluation.Meanwhile,the self-certifying identifi-ers represented the identity information of tunnel routers,and guaranteed the authenticity of the mapping sources.Per-formance analysis and simulation results have shown that the approach provides a satisfying safeguard for the mapping theory.By setting the threshold of different trust value,this approach can effectively inhibit the tunnel routers from em-ploying the mendacious mapping information,and further reduces the hazards of mapping spoofing.